Survei Jentik Nyamuk Anopheles di Desa Maukeli Kecamatan Mauponggo - Helen Ndiki; Apris A. Adu; Ribka Limbu (Universitas Nusa Cendana, 2020)
Malaria is an infectious disease caused by the parasitic plasmodium protozoan parasite. This disease is transmitted through female Anopheles sp mosquito bites. Anopheles mosquito breeding sites can be in the form of fresh water or salt water, ponds that are overgrown with aquatic plants or those that do not plant, rice fields, river mouths where the flow is not swift and small pools filled with rainwater. Maukeli Village is a village that has a lot of rice fields. The purpose of this study was to determine the density of Anopheles mosquito larvae at various breeding places in Maukeli Village, Mauponggo District in 2018. This type of research design was a descriptive survey with a population of all Anopheles sp. existing in the breeding places and breeding places of mosquito larvae Anopheles sp. The samples in this study were all Anopheles mosquito larvae from the results of abduction at breeding places in Maukeli Village. Sampling was carried out accidentally (ie Anopheles mosquito larvae which happened to be available or available to be sampled. The results showed that there were 4 breeding places, namely paddy fields with average density of Anopheles mosquito larvae (12 tail/ cut), river mouths with average density of Anopheles mosquito larvae (8 tail/ cud), pools with average density of mosquito larvae Anopheles (3 tail/ cud) and the lagoon with average density of Anopheles mosquito larvae (5 tail/ cud) while permanent breeding sites are river mouths and temporary breeding sites, such as river mouths, pools and lagoon.